Sequencing and functional characterization of SCARB1 variants in subjects with extreme HDL cholesterol levels. - Gracia-Rubio, Irene; Benito-Vicente, Asier; Lamiquiz-Moneo, Itziar; Bea, Ana María; Marco-Benedí, Victoria; Cabrera-Antón, Endika; Martín, César; Civeira, Fernando; Cenarro, Ana (Journal of Clinical Lipidology, 2026)
• SCARB1 was sequenced in 96 extreme-high-density lipoprotein cholesterol (HDL-C) subjects; 25 variants identified. • Novel c.-177G>T promoter and missense p.(Thr118Ser) were described. • p.(Thr118Ser) and p.(Thr378Met) co-segregate with high HDL-C. • p.(Thr378Met) variant impairs SR-B1–mediated HDL uptake in vitro. Rare variants in SCARB1 , which encodes the high-density lipoprotein (HDL) receptor scavenger receptor class B type 1 (SR-B1), are hypothesized to drive unexplained extreme levels of plasma HDL cholesterol (HDL-C). We sequenced and phenotypically correlated SCARB1 by analyzing individuals with extreme HDL-C levels and characterizing the functional consequences of rare identified variants. SCARB1 was Sanger-sequenced in 96 unrelated participants with extreme HDL-C levels. Clinical, biochemical, and anthropometric data were compared between groups. Bioinformatic tools were used to predict the functional impact of all detected variants. Familial analyses of predicted damaging in silico or not previously described variants was assessed, and HDL uptake was quantified by flow cytometry in HEK293 cells expressing rare SCARB1 variants showing a suggestive pattern of familial segregation. Compared with the high-HDL-C group, low-HDL-C subjects exhibited lower low-density lipoprotein cholesterol and total cholesterol but higher triglycerides, higher body mass index, and a greater frequency of atherosclerotic cardiovascular disease events. Twenty-five SCARB1 variants were identified; 4 of them, c.-177G>T, p.(Thr118Ser), c.843-982G>A and p.(Thr378Met), were predicted to be deleterious. The missense changes p.(Thr118Ser) and p.(Thr378Met) showed a suggestive pattern of segregation with high HDL-C in available pedigrees. Cells expressing p.(Thr378Met) SCARB1 variant showed a reduction in HDL uptake vs wild-type. Rare predicted damaging in silico variant in SCARB1 , p.(Thr378Met), impairs SR-B1-mediated HDL uptake and associates with high HDL-C levels, highlighting SCARB1 as a candidate gene for genetic screening in dyslipidemic patients.